STUDI KELAYAKAN USAHATANI BAMBU PETUNG DI HUTAN BONGOK DESA JETAK KECAMATAN MONTONG KABUPATEN TUBAN - Kartini, Maria Talisia; Pudjiastuti, Agnes Quartina; Khoirunnisa, Ninin (BUANA SAINS, 2023)
This research aimed to determine petung bamboo farming is feasible in the Bongok Forest for forest conservation and restoration. Data analysis used quantitatively, namely farming analysis, feasibility analysis, and sensitivity analysis using the feasibility criteria Gross Benefit Cost Ratio (Gross B/C), Net Benefit Cost Ratio (Net B/C), Net Present Value (NPV), Internal Rate Of Raterun (IRR), Payback Period (PP), and Break Event Point (BEP). The income from farming is Rp. 1,720,750,000 from petung bamboo production for ten years where petung bamboo starts production in the 5th year with a total production of 48,650 stems multiplied by the price of petung bamboo at the farmer's level starting from Rp. 20,000 to Rp. 40,000 is calculated from the 5th year of production until the 10th year with an annual price increase of Rp. 5,000. Income is Rp.1,461,000,311 total income minus total expenditure on petung bamboo farming. Gross B/C is 22.18879511 1. Analysis of investment feasibility criteria shows that petung bamboo farming in the Bongok Forest is feasible. The NPV value of obtaining a profit of Rp. 830,795,931, IRR value 44.51% ( 6%), Net B/C Value of 81,633,855 1, Production BEP of 48650, and BEP price of IDR 4365.420357 and Payback Period can returned for a period of 5,989.